030. Delayed Presentation of Blunt Traumatic Diaphragmatic Hernia 15 Years After Injury: A Case Report - Tsurayya, Zulfa; Fauzie, Rayhan; Krislee, Andre; Waelauruw, Shania Quency Alexandra; Yani, Irhamna Syari (JBN (Jurnal Bedah Nasional); Vol 8 No 2 (2024): Proceeding The 2nd National Conference of Indonesia Surgical EducationDO - 10.24843/JBN.2024.v08.is02.p030, 2024)
Background : Traumatic diaphragmatic rupture is rare with incidence between 0.8-8% and often resulting from blunt or penetrating trauma. We present a case of delayed diaphragmatic hernia in a 41-year-old male, 15 years after blunt abdominal trauma. Case : A 41-year-old male presented with dyspnea and severe abdominal pain. He reported being struck in the abdomen with wood during a gang attack 15 years prior. A year after the accident, he complained of uncomfortable breathing that worsened in the past 6 years. Physical examination revealed decreased breath sounds on the left side and a distended abdomen. Imaging confirmed bowel herniation into the left hemithorax, partial lung collapse, and a mediastinal shift. Emergency laparotomy revealed a 5 cm diaphragmatic defect, massive gastric necrosis, and herniation of abdominal organs into the thoracic cavity. The defect was closed with primary repair, and necrotic gastric tissue was excised and repaired using primary closure with omental patch. The patient recovered well and was discharged on day 11. Conclusion: Diaphragmatic ruptures require prompt surgical repair to prevent complications. Physicians must carefully evaluate trauma history and conduct thorough examinations to improve outcomes in emergency settings.